2018
DOI: 10.1159/000491760
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Breast Cancer Treated with Neoadjuvant Therapy

Abstract: Neoadjuvant therapy (NAT) allows downstaging in some cases of breast cancer. By consequence, it may enable a more conservative surgical approach or make surgery possible in cases ineligible for surgery before NAT. In this article, we review the evidence and management recommendations for optimal surgical treatment in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…Ultrasound has been revealed to be a better predictor for pathologic tumour size than mammography after treatment with neoadjuvant therapy. However, ultrasound is operator dependent, and its accuracy varies [2,5,6]. Mammography has been less specific than CE for detecting presence of residual tumour after therapy, and it adds challenges with mammographically occult tumours and microcalcifications which do not correlate with presence of viable tumours [2].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has been revealed to be a better predictor for pathologic tumour size than mammography after treatment with neoadjuvant therapy. However, ultrasound is operator dependent, and its accuracy varies [2,5,6]. Mammography has been less specific than CE for detecting presence of residual tumour after therapy, and it adds challenges with mammographically occult tumours and microcalcifications which do not correlate with presence of viable tumours [2].…”
Section: Introductionmentioning
confidence: 99%
“…The radiologic evaluation before the start of treatment is discussed in the article on surgical management by Cordoba et al [5] in this focus of Breast Care [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Strategies to mitigate this reality should be carefully considered. The main discussion in this part of the review focuses extensively on the multidisciplinary management of patients, accurate radiological assessment prior to and following treatment, the type of markers and tracers that should be used, and the need to precisely tailor the type of surgery to the response achieved by each and every patient [5].The second contribution offers a comprehensive review covering what has been reported in the literature on neoadjuvant systemic therapy in early/locally advanced breast cancer [6]. Among others, two of the topics addressed are optimal patient selection for neoadjuvant therapy based on clinical and biological features and how best to assess response after chemotherapy (i.e.…”
mentioning
confidence: 99%
“…Moreover, since neoadjuvant therapy allows for the testing of novel drugs before surgery and facilitates preliminary data to support the further development of combinations, these qualities also prove its worth in breast cancer research. As is the case with the management of breast cancer in general, this disease cannot be understood in the neoadjuvant context if it is not separated into the three main subtypes that we recognize in clinical practice: HR-positive, HER2-positive, and triplenegative tumors.For this issue of Breast Care with a focus on 'neoadjuvant treatment in breast cancer', we have selected three papers that bring us up to speed on the very latest research advances and current opportunities within this field [5][6][7].The first of this trio tackles the surgical management of patients after treatment following the neoadjuvant strategy and different approaches to de-escalate breast and axilla surgery [5]. The increased use of neoadjuvant therapy in the treatment of early breast cancer has challenged our surgeons to not only finely tune their techniques towards less extensive surgery but also to take advan-…”
mentioning
confidence: 99%
See 1 more Smart Citation